Analisis Kualitas Layanan Pendidikan Terhadap Kepuasan Mahasiswa Difabel Studi Kasus di Universitas Brawijaya - Stefany, Ekky Retno; Setyowati, Endah; Wike, Wike (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
This study was aimed to investigate the satisfaction level of students with disabilities toward the educational services provided by Brawijaya University based on indicators of Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The popilation was students with disabilities at Brawijaya University, while the sample included 16 respondents determined by the Purposive sampling technique. The result demonstrated the average score of the tangibles (X1) variable, reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) were 4.40, 4.04, 4.11, 3.97, and 3.76, respectively. This showed that respondents gave a positive response (agree) to the indicators of the quality of education service. In addition, the score of the customer satisfaction index (CSI) obtained was 81.26%. Therefore, it is concluded that students with disabilities have so far been “satisfied” with the educational service provided by the university. However, university is expected to improve the quality of education service quality and students’ expectation.